The Effectiveness of Using Canva as a Learning Media on the Vocabulary Mastery of Grade Seven Students of Public Tsanawiyah School 6 Solok - Vina Aryani; Hanomi Hanomi (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
The research background in this study is that mastering vocabulary is very ‎important because vocabulary is one of the elements of the language that ‎must be mastered absolutely by those who learn Arabic. It is necessary to ‎have an educational media that is a means of Canva, which is expected with ‎this media in that students will be more interested and be more effective in ‎learning the Arabic language, especially on proficiency in vocabulary. Then, ‎the research objectives in this study are to find out the result of teaching ‎vocabulary among the seventh-grade students after using the Canva media, ‎and to know the effect of using the Canva media on mastering the vocabulary ‎of the seventh grade students in the Madrasah Tsanawiyah Hukumiyah ‎Islamiyah 6 Solok‏.‏‎ The researcher used the quantitative approach in the ‎experimental research method, with the type of research being Quasi ‎Eksperiment and Non-Equivalent Control Group Design, and the method of ‎collecting data is the test and its tools means questions in oral and written ‎form, and in analyzing the data with a T-test using the SPSS 26 program. ‎However, before the "t" test, the researcher used the SPSS 26 program for a ‎normal test and a test for homogeneity because the data should be normal ‎and homogenous. The results of the research indicated that the students' ‎vocabulary mastery after using the media Canva that out of 32 students there ‎were 32 successful students in the minimum measurement of 70 KKM, with an ‎average value of 81.63. The normal test result using the Kolmogorof Smirnof ‎test with a Sig value of 0.200 found to be greater than 0.05 so that the data is ‎normal. Based on the results of the homogeneity test using the Levene test ‎with a Sig value of 0.009 greater than 0.05, this value indicated homogeneity ‎of the data. And then a "t" test result of Sig. (2-Tailed) It is 0.05 greater than ‎‎0.000. The researchers concluded that the null hypothesis (H0) is rejected ‎and the alternative hypothesis (Ha) is accepted. The difference between two ‎groups was found to be indicative of a significant promotion after using the ‎media Canva in the experimental class, in the sense that the use of the media ‎Canva is effective in vocabulary mastery for students in the seventh semester ‎of the Madrasah Tsanawiyah Hukumiyah Islamiyah 6 Solok‎